Perancangan dan Implementasi Aplikasi Sistem Pemantauan Helm Pendeteksi Kantuk Berbasis Website - Yesaya Thomas Alfa Lanes (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2019)
Microsleep is a drowsiness condition that makes a person fail to respond the surrounding environment for several miliseconds. That condition often occurs in motorcyclists. At this time, the information about motorcyclist's drowsiness condition can not be known directly by the motorcyclist's family. This journal explains the design and implementation of a monitoring and history record system application of the motorcyclist's drowsiness using website with brain sensor to detect drowsiness that embedded to the rider's helmet. Data from brain sensor is received by microcontroller that connected to the internet and then sent the data to the website database in real time. The output of this system is to display a dynamic chart and tables on website www.unsikahelpin.xyz that can be accessed online by the motorcyclist's family. Then there is filtering feature according dates to display the time and date when the driver is drowsy. The motorcyclist's brain history data could be saved as a document file in PDF format.